INTERACTIVE POWER POINT-BASED TEAM GAME TOURNAMENT LEARNING TO INCREASE STUDENTS’ INTEREST IN ISLAMIC EDUCATION - Afi Rizqiyah; Gilbrania Affa; Mas Hanik Nur Maimunah; Ali Uroidli (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
This study examined the implementation of an interactive PPT-based TGT learning model to increase student interest. This research was a Classroom Action Research conducted in class IX B SMP Islam As Sakinah Sidoarjo which consists of 22 students. This class was chosen as the research subject because it showed a lower learning interest in Islamic Educationsubjects compared to class IX A with the application of the same learning method. However, according to the Islamic Educationteacher, this class has greater potential if the students’ interest in learning can be improved. Primary data were collected through observation and questionnaires, then analyzed qualitatively and statistically descriptively. Supported by secondary data obtained through interviews and literature studies to find problems and ensure the availability of facilities, and find out student responses to the learning model applied. The results showed an increase in student interest from pre-action by 62% to 94% after implementing the interactive PPT-based TGT learning model. There was also an increase in the number of active students from 16 students to all students in the class (22 students). It can be concluded that the application of interactive PPT-based TGT learning methods can increase students’ interest in Islamic Education learning. Synergizing the TGT learning model with interactive PPT media is one of the right actions to increase student interest in learning. Teachers who find the problem of lack of student interest in learning can apply the TGT learning model by utilizing interactive PPT media as done in this study. In addition, this study can be a reference for further researchers who want to examine the implementation of TGT learning or interactive PPT media in learning.